Linking ‘toxic outliers’ to environmental justice communities - Mary B Collins; Ian Munoz; Joseph JaJa (Environmental Research Letters, 2016)
Several key studies have found that a small minority of producers, polluting at levels far exceeding group averages, generate the majority of overall exposure to industrial toxics. Frequently, such patterns go unnoticed and are understudied outside of the academic community. To our knowledge, no research to date has systematically described the scope and extent of extreme variations in industrially based exposure estimates and sought to link inequities in harm produced to inequities in exposure. In an analysis of all permitted industrial facilities across the United States, we show that there exists a class of hyper-polluters—the worst-of-the-worst—that disproportionately expose communities of color and low income populations to chemical releases. This study hopes to move beyond a traditional environmental justice research frame, bringing new computational methods and perspectives aimed at the empirical study of societal power dynamics. Our findings suggest the possibility that substantial environmental gains may be made through selective environmental enforcement, rather than sweeping initiatives.